(untitled) (Journal of the College of Basic Education, 2022)
In the midst of the systematic system of the text, the cultural function performs a formal dimension by re-receiving the aesthetic concept and programming that taste mechanism. Hence the research worked on the historical concept of literature that carries the aesthetics of the speech, it a spires the count of literate combining the structure of feelings and feelings with the aesthetic form of language, and what is rooted in the cultured literary a warness in terms of context in the system of aesthetic forms. There must be a new historical study that is a war of the coherence of a culture that is muzzled and killed in the corridors of aesthetic system. The Gothami converged between the theory of cultured criticism and the concept of causes, then we conclude that culture criticism does not remains conditional on aesthetic alone, but rather in an implicit format that uses aesthetic means to pass its faults and ideology .